2010
DOI: 10.1097/tp.0b013e3181c4096c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immunosuppressive Therapy on the Natural History of Genotype 3 Hepatitis-E Virus Infection After Organ Transplantation

Abstract: The rate of chronic HEV-related hepatitis is approximately 60% in solid-organ transplant patients. When possible, the reduction of immunosuppressive drugs targeting T cells should be considered as a first-line therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
203
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(219 citation statements)
references
References 21 publications
8
203
0
8
Order By: Relevance
“…In the later course of infection, typical histological features of chronic viral hepatitis such as predominantly portal inflammation and progressive fibrosis were found. 14,16,28 Our observations illustrate that not only clinical presentation, but also liver histology in cases of HEV under immunosuppression is far from characteristic or even specific. Therefore, histological findings consistent with viral hepatitis should prompt diagnostic workup for HEV.…”
Section: Clinical Coursementioning
confidence: 71%
“…In the later course of infection, typical histological features of chronic viral hepatitis such as predominantly portal inflammation and progressive fibrosis were found. 14,16,28 Our observations illustrate that not only clinical presentation, but also liver histology in cases of HEV under immunosuppression is far from characteristic or even specific. Therefore, histological findings consistent with viral hepatitis should prompt diagnostic workup for HEV.…”
Section: Clinical Coursementioning
confidence: 71%
“…11,12,14,18,[36][37][38][39][40][41][42][43][44][45][46][47][48] A large multicenter retrospective study, which included 85 adult patients with a SOT (kidney-, liver-, kidney-pancreas-, islet-, heart-, and lung-transplants) showed that 34.1% had spontaneous clearance of HEV within the first 6 months after HEV was diagnosed and no HEV reactivation later on, whereas 65.9% developed chronic hepatitis. 49 Interestingly, in contrast to non-immunosuppressed patients who usually present to hospital with jaundice, 50 when HEV was diagnosed, only 32% of patients were symptomatic.…”
Section: Natural History Of Hev Infection In Patients With a Sotmentioning
confidence: 99%
“…49 Several other cases of HEVinduced cirrhosis have been reported. 12,18,33,[36][37][38]40,49 In one study, liver fibrosis rapidly evolved in transplant patients who were chronically infected by HEV, and this led to decompensated cirrhosis and death. 40 Slow HEV quasispecies diversification during the first year after infection has been associated with rapidly developing liver fibrosis.…”
Section: Natural History Of Hev Infection In Patients With a Sotmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past several years, HEV infection in organ transplant patients has garnered much interest. After kidney transplantation, HEV-related liver fibrosis can lead rapidly to cirrhosis [5]. The use of tacrolimus, rather than cyclosporine A, and a low platelet count at HEV diagnosis have been identified as predictive factors for chronic HEV infection [6].…”
mentioning
confidence: 99%